THE IMPACT OF VIRTUAL REALITY AND AUGUMENTED REALITY ON STORRYTELLING. THE FUTURE OF JOURNALISM IN METAVERSE - Georgiana Camelia STANESCU (Social Sciences and Education Research Review)
Metaverse or WEB 3.0 is the environment that combines elements of virtual reality, augmented reality or simply the future of the internet. The Metaverse is currently under development worldwide. It was Facebook founder Mark Zuckerberg who first signaled that this is the next stage of the internet, but he is not the only one involved in building the Metaverse. Silicon Valley IT giants didn't want to miss out this opportunity and are already investing huge sums to secure their place at the forefront of the development of this new medium. Experts say this new universe will make its mark, influence and change almost every industry. In this context, we expect one of the big changes to be felt by journalists and the media industry as a whole. We are already seeing the first steps towards immersive journalism, with journalists working in large global media organizations already using virtual and augmented reality to explain better certain stories and to attract a wider readership. This article will provide a theoretical analysis of the impact that Metaverse can have on the media industry, taking into account the technological steps currently being taken in this direction.